Optimizing NPK Fertilization with Arbuscular Mycorrhizae Inoculation to Enhance Shallot (Allium cepa L.) Performance under Drought Stress - Nabil Hisyam; Saefurrohman; Yonny Koentjoro (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Shallots are a high-value horticultural commodity in high demand due to their role in food security. While the demand for shallots increases significantly each year alongside population growth, it has not been matched by stable production increases due to cultivation constraints—one of which is unfavorable environmental factors such as drought. The low tolerance of the plants to water scarcity and their shallow root systems result in inhibited nutrient absorption and reduced yields. Therefore, efforts are needed to increase shallot production, such as through mycorrhizal inoculation and appropriate NPK fertilization. This study aims to determine the optimal combination of mycorrhizal inoculation dosage and NPK fertilizer dosage to influence the growth and yield of the ‘Tajuk’ shallot variety under drought stress conditions.This research was designed as a two-factor factorial experiment arranged in a Randomized Block Design (RBD). The first factor was the mycorrhiza dose, consisting of four treatment levels: 0 g/plant (Control), 5 g/plant, 15 g/plant, and 25 g/plant. The second factor was the NPK dose, consisting of three treatment levels: 300 kg/ha (Control), 270 kg/ha, and 240 kg/ha. The analysis results showed that the treatment with an NPK dose of 300 kg/ha and a mycorrhiza dose of 25 g/plant significantly increased plant height, root length, chlorophyll content, and dry weight.The prominent advantage of these findings lies in proving that mycorrhizal symbiosis acts as a powerful biological buffer, maximizing Nutrient Use Efficiency (NUE) and significantly enhancing the crop's physiological resilience against water deficit. Based on these results, it is highly recommended that farmers cultivating shallots in drylands or drought-prone areas integrate 25 g/plant of mycorrhizal inoculant with the standard 300 kg/ha NPK fertilization.